Systematic Literature Review on Ozone Dispersion Correlated with Diurnal Concentration Pattern in Urban and Rural Areas - Perdinan; Fardilah, Ratih Dwi; Turyanti, Ana; Aditya Pangestu, Lutfi; Venita Dominica, Maria (Agromet, 2023)
Ground level ozone is known to exhibit a strong daily variation of concentration leading to long-range transport of air pollutants from urban to rural areas. Moreover, the characteristics of O3 relationship between urban, suburban, and rural sites can be explained by O3 photochemical chemistry and meteorological dispersions as indicated by the different result of O3 diurnal pattern. However, little is known about the global phenomenon of diurnal concentration of ozone, meteorological dispersion such as long-range transport, and their correlation with ozone precursors, especially in urban and rural areas. This paper attempt to compare the difference between daily ozone fluctuations in both sites and assess some factors that cause long-range ozone transport from urban and rural areas both in subtropical and tropical areas for global scale. Using systematic literature review analysis with the PRISMA method, it examined 43 peer-reviewed articles published between 2010 and 2022 globally meeting the inclusion criteria. The result showed that the fluctuation patterns of daytime ozone in urban and rural areas are different to those in tropical and subtropical regions, depending on latitude. This was primarily due to the influence of solar radiation and the presence of precursors. Conversely, a slight decrease in ozone rate at night occurs because the precursor was accumulated by the shutdown of photochemical ozone production. Some precursors of ozone from other regions can be transported and accumulated from the long-range transport process in other locations. This paper serves as an initial guideline to analysing the pattern of ozone concentration in urban and rural areas and the factors that influence it.